City branding as a tool of public administration - Bilyk, Maryna; Kratt, Oleh; Pryakhina, Kateryna; Trunina, Iryna (Tworzenie marki miasta jako narzędzie administracji publicznej, 2021)
The article examines the formation of the city brand as a tool of public administration for increased competitiveness. The authors present a definition of ‘city branding’ and marketing features of territorial branding, scientific tools developed for diagnostics, as well as development of the territorial brand, and directions of promotion of the city brand as a factor of increasing its competitiveness. The purpose was a theoretical and practical justification for the formation of the city’s brand as a way to increase its competitiveness. The methodological basis of the study was a set of theoretical and empirical methods of scientific knowledge: theoretical generalization in order to clarify the basic theoretical and methodological foundations of the concept of branding the city; analysis and synthesis in determining the strategic directions and target audiences of the city brand; the formation of directions for the promotion of the city brand; visual of the results of the study.
Biblioteka Regionalisty, 2021, Nr 21, s. 15-27
Keywords: brand; city branding; territory branding; public administration; marka; branding miasta; branding terytorium; administracja publiczna